Chloroquine Enhances Chemosensitivity of Breast Cancer via mTOR Inhibition - Zhihao Lin; Yuting Xu; Mifang Li; Yibiao Liu; Jianbo Yu; Lingyan Zhang (Biomedicines)
Background: Chloroquine (CQ) has been extensively validated for its safety as an antimalarial drug. The treatment regimen combining CQ with 5-fluorouracil (5-FU) has demonstrated promising antitumor effects in both in vitro and animal models. However, the clinical application of this combination therapy still faces numerous challenges, primarily due to the unelucidated mechanistic underpinnings. Methods: We validated the synergistic effect of CQ in antitumor therapy using 5-fluorouracil and N-acetylcysteine. Subsequently, we employed lysosomal pH probes and inhibitors (5-BDBD and bafilomycin A1) to verify the mechanism of CQ in synergistic antitumor therapy. Finally, the therapeutic efficacy and underlying mechanisms of CQ were further confirmed through in vivo experiments. Results: Here, we found that CQ can inhibit the ATP-induced activation of mammalian target of rapamycin (mTOR), enhancing the inhibition of 5-FU on the proliferation and survival of tumors. Mechanistically, CQ affects the lysosomal pH value, leading to the inhibition of P2X4 receptor activity. The ATP-P2X4-mTOR axis is consequently disrupted, resulting in the weakened activation of mTOR. Conclusions: Our findings suggest that CQ may inhibit ATP-induced mTOR activation by suppressing P2X4 receptor signaling, thereby altering the apoptosis resistance of tumors. The combination of CQ and 5-FU represents a promising therapeutic strategy, particularly for mTOR-hyperactivated malignancies refractory to conventional chemotherapy. These findings not only advance our understanding of the mechanisms underlying CQ-based combination therapy but also highlight the therapeutic potential of pharmacologically targeting mTOR and its alternative pathways in combination chemotherapy regimens.